DIFFERENTIAL DIAGNOSIS BETWEEN KAWASAKI DISEASE AND ACUTE INFECTIOUS DISEASES – A CASE REPORT - Mateiko, Halyna Bohdanivna; Pylyuk, Iryna Ihorivna; Matvisiv, Mariana Vasylivna; Horbal, Nataliia Bohdanivna; Berezna, Tamara Hryhorivna (Eastern Ukrainian Medical Journal, 2025)
Introduction. Kawasaki disease is a relatively rare but severe acute febrile disease characterized by vasculitis. It represents a unique challenge in pediatrics due to its potential for coronary artery complications and the necessity for prompt recognition and treatment. Materials and methods. The study was conducted at the Ivano-Frankivsk Regional Children Clinical Hospital of the Ivano-Frankivsk Regional Council. A clinical case of Kawasaki disease in a child was analyzed. The research was carried out in accordance with the principles of the Helsinki Declaration. The research protocol was approved by the Local Ethics Committee of the institution. Informed consent of the child's parents was obtained for the research. Case presentation. We are presenting a clinical case of Kawasaki disease in a 5-year-old Ukrainian girl who was diagnosed with acute respiratory disease, tonsillopharyngitis. After the antibacterial therapy, a spotted-papular rash appeared, and the doctor suspected infectious mononucleosis. On the 7th day of the illness, signs of conjunctivitis and pain in the lower extremities appeared, and on the 8th day of the disease, the child was referred to a hospital. Based on the clinical signs and test results, the final diagnosis of Kawasaki disease was established. Upon admission, mild anemia (hemoglobin – 100 g/L), leukocytosis (16.86×109/L), thrombocytosis (1147×109/L), and an elevated erythrocyte sedimentation rate (105 mm/h) were detected. Biochemical blood tests revealed hypoalbuminemia (34.9–10.8 g/L), a decreased A/G index (0.12), and significantly increased D-dimer (6051.3 μg/ml) and C-reactive protein (185.1 mg/l) levels. Echocardiographic examination revealed expansion of the coronary arteries and regurgitation of the tricuspid valve. The patient received intravenous human immunoglobulin 10% at a dosage of 2 g/kg IV for 3 days, acetylsalicylic acid, 10 mg/kg ibuprofen, infusion therapy with glucose-salt solutions, and oral rehydration. Against the background of treatment, the child's condition stabilized, and on the 10th day after admission, with improvement, she was discharged from the hospital. Conclusion. The present case demonstrates that patients with Kawasaki disease need a multidisciplinary approach for timely diagnosis and treatment. Disease manifestations are nonspecific, and doctors often consider them to be signs of more common conditions, such as acute respiratory infections, tonsillitis, and infectious mononucleosis.